The Handbook of bilingual and multilingual education - Wright, Wayne E.; Boun, Sovicheth; García, Ofelia (Blackwell handbooks in linguistics, 2017)
"Represents the first comprehensive reference work that covers bilingual, multilingual, and multicultural educational policies and practices around the world"--